Bidirectional associations between family conflict and child behavior problems in families at risk for maltreatment. (November 2022) - Morelli, Nicholas M.; Hong, Kajung; Elzie, Xavier; Garcia, Jackelyne; Evans, Meghan C.; Duong, Jacqueline; Villodas, Miguel T.
Abstract: Background: Children's exposure to family conflict is associated with the development of behavior problems. However, it remains unclear whether this association (1) functions bidirectionally and (2) exists independent of more severe forms of violent victimization. Objective: The present study aimed to examine bidirectional and transactional associations between family conflict and children's behavioral problems, controlling for time-varying violent victimization experiences. Invariance testing examined whether these models differed by gender and by maltreatment status prior to initial recruitment. Participants and setting: Participants were caregiver-child dyads identified prospectively as being at risk for maltreatment and family violence exposure prior to age four ( N = 1281; 51.4 % female; 74.6 % persons of color). Methods: Caregivers were interviewed prospectively about family conflict, children's aggressive and delinquent behavior, and children's victimization experiences at child ages 6, 8, and 10. Results: After controlling for prior victimization, significant cross-lagged bidirectional associations were identified between family conflict and child behavior problems. Indirect effects from age 6 to age 10 externalizing problems through age 8 family conflict were not supported. Several bidirectional paths were stronger among boys than girls. Results revealed little evidence for moderation by prerecruitment maltreatment status. Conclusions: Findings support a conceptualization of the family-child relationship that is reciprocal in nature and highlight the importance of non-violent, everyday negative family processes. Interventions aiming to improve child behavior problems by targeting severely dysfunctional family processes should also address non-violent, lower-level patterns of negative family interactions, such as everyday instances of blame, criticism, nonacceptance, and favoritism.